Exploring the human cerebral cortex using confocal microscopy. (January 2022) - Pesce, Luca; Laurino, Annunziatina; Scardigli, Marina; Yang, Jiarui; Boas, David A.; Hof, Patrick R.; Destrieux, Christophe; Costantini, Irene; Pavone, Francesco Saverio
Abstract: Cover-all mapping of the distribution of neurons in the human brain would have a significant impact on the deep understanding of brain function. Therefore, complete knowledge of the structural organization of different human brain regions at the cellular level would allow understanding their role in the functions of specific neural networks. Recent advances in tissue clearing techniques have allowed important advances towards this goal. These methods use specific chemicals capable of dissolving lipids, making the tissue completely transparent by homogenizing the refractive index. However, labeling and clearing human brain samples is still challenging. Here, we present an approach to perform the cellular mapping of the human cerebral cortex coupling immunostaining with SWITCH/TDE clearing and confocal microscopy. A specific evaluation of the contributions of the autofluorescence signals generated from the tissue fixation is provided as well as an assessment of lipofuscin pigments interference. Our evaluation demonstrates the possibility of obtaining an efficient clearing and labeling process of parts of adult human brain slices, making it an excellent method for morphological classification and antibody validation of neuronal and non-neuronal markers.